2022
DOI: 10.36348/merjd.2022.v02i01.001
|View full text |Cite
|
Sign up to set email alerts
|

Compositions "Nanosilica – Mineral Fillers – Epoxy Resin" For OutClinical Dental Prevention and Self-Treatment of Carious and Traumatic Dental Damages

Abstract: In our new experimental works, the existence of highly filled epoxy-mineral compositions capable of filling and restoring damages of teeth, outside of clinical conditions, is shown. These hypotheses found confirmation in the obtained results of dental repair on volunteers. The tooth powders and epoxy-composites from cheap available components, for use by non-specialists in domestic and non-clinical conditions – were developed and proposed. These results will be very useful for people and communities who, for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The Chuiko Institute of Surface Chemistry was among the first institutions in the world to create its own Laboratory of Biocompatible Materials. It developed some of the first photopolymer highly filled compositions for prosthetics and filling in the USSR and the world, documented in a number of articles, patents and dissertations [1][2][3]. Accordingly, the Ukrainian SSR and then Ukraine became the place for the first introduction of both innovative photopolymer dental pastes (Oxomat, Stomadent, Esta, etc.)…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%
See 1 more Smart Citation
“…The Chuiko Institute of Surface Chemistry was among the first institutions in the world to create its own Laboratory of Biocompatible Materials. It developed some of the first photopolymer highly filled compositions for prosthetics and filling in the USSR and the world, documented in a number of articles, patents and dissertations [1][2][3]. Accordingly, the Ukrainian SSR and then Ukraine became the place for the first introduction of both innovative photopolymer dental pastes (Oxomat, Stomadent, Esta, etc.)…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%
“…Our experience has shown that this is possible when using ordinary available epoxy resins. The prospects for self-restoration with epoxy materials were described in general terms for the first time in our first publications [1][2][3], and above all in this publication [4].…”
Section: Dental Problems: Can We Help Ourselves?mentioning
confidence: 99%